Gerontological intervention with caregivers of Seniors - Sevilla Segura, Katia Vanesa (2011)
Elderly people’s caregivers expose themselves while assuming a responsibility that, if they do not have in-depth knowledge about, could lead them to a wearing occupation. Consequently, the next generation of elderly people could have an inferior quality of life than their predecessors. Gerontology professionals have the duty to realize this situation, and develop skills that enable an appropriate, efficient, and effective intervention.